2022
DOI: 10.1093/nar/gkac234
|View full text |Cite
|
Sign up to set email alerts
|

SETDB1 fuels the lung cancer phenotype by modulating epigenome, 3D genome organization and chromatin mechanical properties

Abstract: Imbalance in the finely orchestrated system of chromatin-modifying enzymes is a hallmark of many pathologies such as cancers, since causing the affection of the epigenome and transcriptional reprogramming. Here, we demonstrate that a loss-of-function mutation (LOF) of the major histone lysine methyltransferase SETDB1 possessing oncogenic activity in lung cancer cells leads to broad changes in the overall architecture and mechanical properties of the nucleus through genome-wide redistribution of heterochromatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…This implies that the B cell infiltration in LUAD may be associated with the NK cell population as well. Moreover, new research shows that SETDB1 fuels the phenotype of lung cancer by modulating the epigenome and resists anti-CTLA4 and anti-PD1 combination therapy ( Griffin et al, 2021 ; Zakharova et al, 2022 ). Pasquarella et al (2016) also detected an increased level of Xbp1 expression in SETDB1-deficient B cells.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the B cell infiltration in LUAD may be associated with the NK cell population as well. Moreover, new research shows that SETDB1 fuels the phenotype of lung cancer by modulating the epigenome and resists anti-CTLA4 and anti-PD1 combination therapy ( Griffin et al, 2021 ; Zakharova et al, 2022 ). Pasquarella et al (2016) also detected an increased level of Xbp1 expression in SETDB1-deficient B cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SETDB1 is a histone H3K9 methyltransferase, which is often up-regulated in different types of tumors (Lazaro-Camp et al, 2021). In lung cancer cells, the inactivation of the SETDB1 gene leads to recovery features of a normal epithelial phenotype, including an increase in spatial cis-contacts within the B-compartment and a decrease in inter-compartment interactions (Zakharova et al, 2022).…”
Section: Level 3-compartmentsmentioning
confidence: 99%
“…Loop is a fundamental spatial regulatory structure that generally occurs between enhancers and promoters within TADs, which is necessary for gene expression [23]. Existing study has demonstrated the important regulatory role of 3D chromatin structure in gene expression [24]. It is reported that perturbations of 3D genome organization caused by the loss of H3K9 methylation activity will affect the gene expression patterns [25].…”
Section: Introductionmentioning
confidence: 99%
“…Existing study has demonstrated the important regulatory role of 3D chromatin structure in gene expression [24]. It is reported that perturbations of 3D genome organization caused by the loss of H3K9 methylation activity will affect the gene expression patterns [25]. The interaction network between super enhancers (SE) and super silencers, as well as key transcription factors (TFs) also can regulate gene expression [26].…”
Section: Introductionmentioning
confidence: 99%